2019
DOI: 10.1097/md.0000000000015004
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile-associated diarrhea following the therapy with antibiotic and proton pump inhibitors in a 77-year-old man with several comorbidities

Abstract: Rationale: Clostridium difficile -associated diarrhea (CDAD) remains a persistent challenge, with substantially increased incidence and severity. The rising burden of CDAD requires urgent identification of preventable risk factors. Patients concerns: A 77-year-old man with the symptoms of abdominal pain and watery diarrhea was readmitted to the hospital, who received cephalosporins and proton pump inhibitors (PPIs) during the initial hospitalization for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Moreover, PPIs are currently over-the-counter medications in many countries; therefore, their use is often not monitored by a healthcare specialist. Notable, side effects of long-term use of PPIs are gaining increasing attention, especially cognitive impairment [59]. Wijarnpreecha et al[10] performed pooling analyses regarding the association of dementia and PPI users, and indicated an increased risk of dementia and Alzheimer’s disease (AD) among PPI users.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PPIs are currently over-the-counter medications in many countries; therefore, their use is often not monitored by a healthcare specialist. Notable, side effects of long-term use of PPIs are gaining increasing attention, especially cognitive impairment [59]. Wijarnpreecha et al[10] performed pooling analyses regarding the association of dementia and PPI users, and indicated an increased risk of dementia and Alzheimer’s disease (AD) among PPI users.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating data illustrate the potential risks associated with long-term PPI therapy, including pneumonia, spontaneous bacterial peritonitis, gastric cancer, vitamin B12 deficiency, Clostridium difficile -associated diarrhea, myocardial infarction, hypomagnesemia, chronic kidney disease, and hip fracture[5-10]. Regarding concerns over liver adverse effects, a previous meta-analysis showed that PPIs increase the risk of hepatic encephalopathy (HE) in patients with hepatic failure[11].…”
Section: Introductionmentioning
confidence: 99%
“… 30 , 31 This risk is further increased to a greater extent by concurrent use of broad-spectrum antibiotics, especially cephalosporins, fluoroquinolones, clindamycin and some penicillins. 31 , 32 , 33 There is an associated increased risk of both community-acquired pneumonia (CAP) and hospital-acquired pneumonia (HAP) in patients exposed to PPIs. 9 , 13 , 34 The identification of preventable risk factors and careful patient selection is essential in prevention of these complications.…”
Section: Discussionmentioning
confidence: 99%